Social responsibility dimension in Islamic investment: a survey of investors' perspective in Malaysia - Barom, Mohd Nizam (Bloomsbury Qatar Foundation, 2015)
This paper seeks to explore the level of support investors attach to the social responsibility dimension in Islamic investment. The call to address this ‘neglected’ dimension as observed in the practice of Islamic finance is emphasized in the face of the rapidly growing Socially Responsible Investment (SRI) industry in the West and other developed markets, where various social, ethical, and environmental considerations are central to the investment decision. The empirical analysis of the paper is based on a survey conducted on Malaysian investors of Islamic funds from three leading fund management companies. The overall result reveals that the investors in general place a hierarchy in the elements they considered important; the observance of fiqh injunctions is ranked as the most important consideration, followed by economic and social responsibility dimensions. The findings are based on both the descriptive analysis and the composite scales constructed as a result of an exploratory factor analysis, which provide statistical evidence on the nature of social responsibility dimensions being acknowledged by the respondents as part of an important underlying factor in their investment decision. Despite being overpowered by the economic aspect, the findings suggest that social responsibility criteria in investment are perceived as important by a majority of the investors, and substantial proportion of the respondents consider the dimension to be as equally or more important than the economic dimension. Further analysis reveals that the level of importance investors attached to the social responsibility dimension is determined by ethnicity, religion, level of commitment to Shariah principles in investment, income, age, level of SRI awareness, as well as gender, marital status and participation in pro-social activities. The favorable attitude of the respondents on the importance of social responsibility issues can be an encouraging precursor to the incorporation of these concerns into Islamic investment practices.